1973
DOI: 10.1002/ajpa.1330380267
|View full text |Cite
|
Sign up to set email alerts
|

Handedness in the common marmoset (Callithrix jacchus)

Abstract: For about 20 months the development of hand preferences in 21 experimentally naive common marmosets (Callithrix jacchus ) was examined in 15 different tests. Test preferences were compared with their spontaneous behavior preferences in such contexts as feeding, grooming, play, and others. In the spontaneous use of the hands, only eight animals showed a significant lateral preference ( 2 left-handed, 6 right-handed). During the test period, however, the number of handed marmosets increased to 19 ( 5 left-handed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
4

Year Published

1980
1980
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 9 publications
3
37
4
Order By: Relevance
“…This is expected because factors such as predation and migration that constitute the main determinants of the sex biased composition observed in wild groups for adult animals (MOORE & ALl, 1984;DUNBAR, 1988) do not interfere at this age. Similar results were reported by ROTHE et al (1987) and Box and HUBRECHT (1987), for captivity conditions and also by ARA1) JO (1996) in a wild study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is expected because factors such as predation and migration that constitute the main determinants of the sex biased composition observed in wild groups for adult animals (MOORE & ALl, 1984;DUNBAR, 1988) do not interfere at this age. Similar results were reported by ROTHE et al (1987) and Box and HUBRECHT (1987), for captivity conditions and also by ARA1) JO (1996) in a wild study.…”
Section: Discussionsupporting
confidence: 89%
“…Our results also show that in our colony twins were the most frequent litter size for both captive-born and wild-caught females, in contrast to the data reported by POOLE and EVANS (1982), BOX andHUBRECHT (1987), andROTHE et al (1987) who found a higher incidence of triplet births. These last authors have argued that this increase in the frequency of triplet deliveries in captive population s may be a temporary effect and KILBORN et al (1983) attributed this effect to the high amounts of protein in the diet of captive animals.…”
Section: Discussioncontrasting
confidence: 57%
“…Their initial preferences are weak, largely task specific, and unpredictive of later preferences (Warren, 1977). Marmosets are ambidextrous in spontaneous activities like play, feeding, and exploiting materials (Rothe, 1973). Ettlinger, Blakemore, and Milner (1968) did not use the early responses of their experimentally naive monkeys to specify their hand preferences because initial responses tend to be atypical.…”
Section: Temporal and Situational Constancymentioning
confidence: 99%
“…Marmosets also display discrepant hand preferences on different tests of manipulation (Rothe, 1973). The hand preferences of monkeys are also influenced by context effects, in that performance on a specific test, and its correlations with other tests, varies among experiments with different series of monkeys, apparently as a function of which other tests are presented in the test battery, distribution of practice on the several tasks, and other details of experimental procedure.…”
Section: Temporal and Situational Constancymentioning
confidence: 99%
“…In the first study, we examined the utility of urinary cortisol excretion as a measure of psychosocial stress in a context distinct from reproductive function. Sibling conflicts within family groups ("sibling-fights") occur commonly in marmoset and tamarin social groups [Kleiman, 1979;Sutcliffe & Poole, 1984;McGrew & McLuckie, 1986;Rothe et al, 1988;Inglett et al, 1989] and while rarely injurious, these conflicts constitute a significant source of social disruption within groups. We wished to test, therefore, whether known or suspected psychosocial stressors such as sibling fights could produce changes in cortisol excretion.…”
Section: Introductionmentioning
confidence: 99%